Application Analysis of Positive-Pressure Connector in Invasive Blood Pressure Monitoring in Coronary Interventional Therapy - Wang, Aili; Liu, Junying; Peng, Wanzhong; Jiang, Yang; Guo, Lina; Xu, Zesheng (Frontiers in Surgery, 2021)
BACKGROUND In order to reduce the risk of invasive blood pressure monitoring and improve the safety and efficiency, this paper mainly analyzes the effectiveness and safety of using positive pressure connector for invasive blood pressure monitoring in patients with coronary artery interventional therapy, so as to improve the invasive blood pressure monitoring method. AIM To study and analyze the application of positive pressure connector in invasive blood pressure monitoring in coronary interventional therapy. METHODS From October 2017 to October 2019, a total of 120 patients admitted to Cangzhou Central Hospital, Cangzhou, Hebei, China for coronary interventional therapy with invasive blood pressure monitoring were selected and divided into a control group and an experimental group by drawing lots with 60 patients in each group. Positive pressure connector was used for invasive blood pressure detection in the experimental group, and heparin cap connector was used for invasive blood pressure detection in the control group. The effectiveness and safety of blood pressure monitoring in the two groups were compared, and the influence of different joints on invasive blood pressure monitoring was analyzed. RESULTS The influencing factors of puncture efficiency in the experimental group (6.67%) were significantly lower than those in the control group (30.00%) (P<0.05). There was no significant difference in catheter bending between the experimental group and the control group (P>0.05). The experimental group exhibited a remarkably higher puncture safety rate (93%) compared to the control group (67%)(P<0.05). There was no significant difference in arterial blood pressure between the two groups with different indwelling time (P>0.05).The frequency of extubation and reinsertion in the experimental group was significantly lower than that in the control group (P<0.05). Factors influencing puncture safety in the experimental group were significantly lower than those in the control group (P<0.05). CONCLUSION: The use of positive pressure connector for invasive blood pressure monitoring in patients with coronary artery interventional therapy can greatly improve the safety of blood pressure monitoring and reduce the suffering of patients. Therefore, the application of positive pressure connector in invasive blood pressure monitoring is worthy of promotion and application in clinical practice.